Grace in Times of Friction: The Complexity of Social Resilience - Vasu, Norman (2016)
THE BRITISH public’s reaction to acts of terrorism over the past two years has been instructive. Besides being generally unruffled by terror attacks and carrying on with normal life, the public has also used the internet to thumb its nose at terrorism. After the London bombings of 7 July 2005, the internet was employed by the public to declare “We’re not Afraid”. In Glasgow, the internet once gain has been deployed as a rallying tool. A tribute site has been created for John Smeaton (www.johnsmeaton.com), an airport baggage handler who, upon seeing a burning man attacking a police officer, pitched in to help. His interviews are available at the site and the public can use Paypal to buy him a pint of beer in recognition of his bravery.